Designing an Open Innovation Framework for Digital Transformation Based on Systematic Literature Review - Abdurrahman Abdurrahman; Aurik Gustomo; Eko Agus Prasetio; Sonny Rustiadi (Journal of Information Systems Engineering and Business Intelligence, 2022)
Background: Innovation is a critical success factor of digital transformation (DX). Previous research has shown that open innovation (OI) can help companies accelerate DX and improve their business performance. Objective: This study develops a conceptual OI framework to support DX (OIDX) and provides an overview of the dimensions. OI in this study refers to Open Innovation 2.0.  Methods: We review previous research on OI dimensions, identify the activities, and map them along with the challenges that lead to failure. With this, we develop a framework to meet the needs and solve problems of OI implementation. Results: The OIDX framework has a comprehensive dimensional scope consisting of three perspectives, eight dimensions, and 26 sub-dimensions. The perspectives are enablers, activities, and output, and the dimensions are OI governance, external environment, internal climate, digital technology, importing mechanisms, collaboration, protection mechanisms, and export mechanisms. Conclusion: This study highlights the importance of defining dimensions to establish General System Theory. The practical application of this framework is to build an OI ecosystem that can increase the internal and external values of an organisation. The OI framework provides OI success parameters and criteria for building the OI maturity framework in future research. Keywords: DX, Innovation, Open Innovation, Open Innovation Framework